CONSUMPTIVISM IN THE GENDER ROLE IN NI NYOMAN SANI’S WORKS OF ART - Luh Suartini; Hardiman . (E-Journal of Cultural Studies, 2023)
All this time in visual art in Bali a woman has often been placed as an object per se.Actually, in the visual work of women artists in Bali there is found an ideology that worksbehind it. This article reveals and describes the gender ideology that works behind thevisual representation of Ni Nyoman Sani that is why a descriptive qualitative study is usedby using postmodernism theory, visual semiotic theory, gender theory, ideology theory,and psychoanalysis theory to reveal the problem. This article concludes that the genderideology works behind Ni Nyoman Sani’s work, that is, concerning the consumptivism ofthe gender role in its use. It is hoped that this discussion can give us a broader and deeperunderstanding of the gender ideology that works behind Ni Nyoman Sani’s creativeprocess. Keywords: consumptivism, gender role, ni nyoman sani.